2020
DOI: 10.1016/j.jiec.2020.08.031
|View full text |Cite
|
Sign up to set email alerts
|

An alternative to cyanide leaching of waste activated carbon ash for gold and silver recovery via synergistic dual-lixiviant treatment

Abstract: This study reports the development of a hydrometallurgical treatment for activated carbon ash (ACA); a waste product of the carbon-in-pulp (CIP) process used in the gold mining industry, rich in adsorbed precious metals. After an initial screening of known leaching chemistries, the research focusses on dual-lixiviant (thiourea and thiocyanate) and thiourea systems, both of which have lower environmental impact than traditional cyanide leaches. Comparing ferric sulfate and hydrogen peroxide as oxidants showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 62 publications
0
7
1
Order By: Relevance
“…Recently, the synergistic effect of thiourea and thiocyanate on gold extraction from activated carbon ashes in the presence of H 2 O 2 as the oxidant has been investigated. In this study, 0.13 M thiourea and 0.78 M thiocyanate extracted 89% gold in 100 min; the leaching rate is significant, while the reagent concentration is still higher than that in the present article . Generally, it can be concluded that the gold concentration, ore type, and ore mineral composition affect thiocyanate consumption and optimum leaching conditions.…”
Section: Literature Comparisoncontrasting
confidence: 47%
See 1 more Smart Citation
“…Recently, the synergistic effect of thiourea and thiocyanate on gold extraction from activated carbon ashes in the presence of H 2 O 2 as the oxidant has been investigated. In this study, 0.13 M thiourea and 0.78 M thiocyanate extracted 89% gold in 100 min; the leaching rate is significant, while the reagent concentration is still higher than that in the present article . Generally, it can be concluded that the gold concentration, ore type, and ore mineral composition affect thiocyanate consumption and optimum leaching conditions.…”
Section: Literature Comparisoncontrasting
confidence: 47%
“…In this study, 0.13 M thiourea and 0.78 M thiocyanate extracted 89% gold in 100 min; the leaching rate is significant, while the reagent concentration is still higher than that in the present article. 42 Generally, it can be concluded that the gold concentration, ore type, and ore mineral composition affect thiocyanate consumption and optimum leaching conditions. Overall, the results of the present study, high gold recovery, and optimal leaching conditions represent unique contributions to the literature by using the design of experiments approach, conducting leaching experiments on the oxide ore rather than the high-purity gold disc and more common sulfide ores, not adding a synergist to reduce the reagent consumption, employing a high pulp density, and evaluating leaching kinetics along with effect of different metal ions.…”
Section: Literature Comparisonmentioning
confidence: 99%
“…The second barrier is the relative weakness of the metal binding by the AC matrix, essentially due to variable and inconsistent functional group distribution on the surface [57]. Indeed, the reversibility of platinum group metal adsorption on to activated carbon is the phenomenon which underpins gold hydrometallurgy [58].…”
Section: Activated Carbonmentioning
confidence: 99%
“…Indeed, the application of different thiourea-based leaching systems is usually accompanied by a high yield of mobilized Au. Thus more than 80% of Au can be mobilized by thiourea leaching from such wastes as activated carbon (2.9 µg/g of Au) [85], wastes of amalgamation and cyaniding processes (1.7-8.5 µg/g of Au) [86], and Cu smelting slag (0.44-0.46 µg/g of Au) [87]. Furthermore, thiourea-based leaching systems are often used for extraction of Au from electronic wastes [14,68,76,83,84,88,89].…”
Section: Use Of Secondary Materials For Au Leachingmentioning
confidence: 99%